Status of User-Centric E-Governance Practices in North India - Jindal, Neena; Sehrawat, Anil; Medury, Y. (Prabandhan: Indian Journal of Management, 2016)
Information and communication technologies (ICT) suggest to the government new possibilities for providing citizens better and more efficient services according to their convenience. In the modern age of online services, the citizens may expect better services from the government. The user centric approaches of the government services motivate the user to utilize and avoid criticism. The user needs to be placed at the center of development, and provisions need to be in place for electronic public services. Simultaneously, it is required to check the impact of the new services on customers. User satisfaction may have a definite decisive influence on large-scale adoption and use of E-government services. This paper attempted to find out the extent of use and impact of e-governance on the welfare services of the government in six Indian states- Chhattisgarh, Haryana, Himachal Pradesh, Punjab, and Uttarakhand.